Ataxia, Ophthalmoplegia, and Areflexia: What Would You Think? - N. Karsan; P. Fletcher; I. Bodi; B. K. MacDonald (Case Reports in Neurological Medicine)
We present here a case of carcinomatous meningitis presenting as Miller Fisher syndrome (MFS). There are four further cases described in the literature with evidence of tumour invasion within the central nervous system (CNS) shown either in cerebrospinal fluid examination or on histology. There are further five cases described in which an association between cancer and a Miller Fisher phenotype has been shown. Some of these have identified antiganglioside antibodies in the serum and, in one case, also showed antibodies deposited within the primary tumour itself. This raises a question as to whether there is a paraneoplastic form. It would be informative when further cases present in this way to histologically examine for malignant CNS invasion, and the presence of antiganglioside antibodies in both the malignant primary and areas of nervous system thought to be affected by MFS.